Korean Wave's Influence on BT21 Purchases in Indonesia: Pengaruh Korean Wave terhadap Pembelian BT21 di Indonesia - Putri, Rachelita Agista Nasruhan; Hariasih, Misti (Indonesian Journal of Innovation Studies, 2024)
The influence of Korean Wave Brand Ambassadors and Influencers on purchasing decisions for BIS "BT21" products was examined in this study. Korean Wave, a phenomenon of Korean pop culture, has significantly impacted global markets. Companies leverage this trend to boost product sales through brand ambassadors and influencers. Despite its popularity, the specific impact on consumer purchasing decisions remains underexplored. This study aims to fill this gap by analyzing the effects of Korean Wave, Brand Ambassadors, and Influencers on BT21 product purchasing decisions in Sidoarjo, East Java. Using a quantitative approach, the research sampled 96 consumers who have purchased BT21 products, employing the Lemeshow formula for sampling. Data were collected through a questionnaire with a 5-point Likert scale and analyzed using SmartPLS version 3.0 software. The results indicated that the Korean Wave positively and significantly influences purchasing decisions for BT21 products. Similarly, Brand Ambassadors and Influencers also have a positive and significant impact on purchasing decisions. The findings suggest that the Korean Wave, alongside strategic use of Brand Ambassadors and Influencers, can effectively enhance consumer loyalty and boost product sales. These results have important implications for marketing strategies, particularly in leveraging cultural phenomena and influential figures to drive consumer behavior. Highlight: Significant Impact: Korean Wave, Brand Ambassadors, and Influencers significantly influence BT21 purchasing decisions. Quantitative Analysis: Study used quantitative methods and SmartPLS software for data analysis. Marketing Strategies: Findings highlight the importance of leveraging cultural trends and influential figures in marketing. Keywoard: Korean Wave, Brand Ambassadors, Influencers, BT21, Consumer Behavior